1997
DOI: 10.1007/bf02632914
|View full text |Cite
|
Sign up to set email alerts
|

Studies on buffalo babesiosis in Hubei Province, China

Abstract: The present paper summarises our recent studies on buffalo babesiosis in the Hubei province of China. It describes the pathogen and the epidemiology of the disease, the tick vector and its biology, control, immunological diagnosis, methods of in vitro cultivation of the pathogen and their practical applications. The identify of the pathogen is discussed in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…In contrast, bovine cattle, exotic in the Americas, has only recently come in contact with the vector and pathogen and may thus be highly susceptible to tick infestation and pathogen infection. In this context, it is noteworthy mentioning that clinical cases of babesiosis are commonly reported in water buffalos from China and India, which can be lethal in untreated animals 5,6 . Originally it had been thought that buffalo babesiosis is, as bovine babesiosis, caused by B. bovis .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, bovine cattle, exotic in the Americas, has only recently come in contact with the vector and pathogen and may thus be highly susceptible to tick infestation and pathogen infection. In this context, it is noteworthy mentioning that clinical cases of babesiosis are commonly reported in water buffalos from China and India, which can be lethal in untreated animals 5,6 . Originally it had been thought that buffalo babesiosis is, as bovine babesiosis, caused by B. bovis .…”
Section: Resultsmentioning
confidence: 99%
“…However, recent evidence demonstrates that the causative agent of buffalo babesiosis is B. orientalis. 5,7 B. orientalis can be distinguished from B. bovis by its smaller size and different morphology and is transmitted by Rhipicephalus haemaphysaloides. 5 Although R. haemaphysaloides feeds on cattle, it has been shown that parasitemia of B. orientalis does not develop and that it is nonpathogenic for bovines 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that several parasites can cause buffalo babesiosis, including Babesia bovis , Babesia bigemina and Babesia orientalis [ 4 , 5 ]. Babesia orientalis was identified to be transmitted by Rhipicephalus haemaphysaloides in its original description in 1997 [ 6 , 7 ]. Clinical symptoms for B. orientalis infection include anemia, fever, icterus and hemoglobinuria, and it can cause death in serious cases [ 3 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…em búfalos (Liu et al 1997, Terkawi et al 2011, estes estudos ainda são raros quando se refere a Anaplasma marginale. No Brasil, Corrêa (2011) observou que a soroprevalência de A. marginale em bubalinos é bem distinta dos valores observados para bovinos.…”
Section: Discussionunclassified